Perancangan Sistem Informasi Geografis (SIG) Berbasis Web untuk Penyediaan Informasi Fasilitas dan Personalia di Universitas Lampung - Kurnia Muludi; Anie Rose Irawati; Eko Priyanto (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2013)
AbstractThe condition of a location can be seen and known through a map. Even though The University of Lampung has a campus map in a form of paper, still the data displayed in this form is very limited. This map has not been used to display information related to the existing facilities and personnel of the University of Lampung. This research design a web based Geographic Information System (GIS) focusing on information of lecturer and his/her department unit. This web based GIS can be used as a tool for visitors and academics to obtain information on faculty unit, building, facilities, as well as the map of the University of Lampung. This web based GIS is developed using several open source software which are QuantumGIS, MapServer, Pmapper Framework and MySQL database. Pmapper Framework increase Â speed, accuracy, convenience and consistency in the development of applications that use MapServer.Keywords : facilities, map, MapServer, Pmapper framework, The University of Lampung, web based GIS.